2007
DOI: 10.1186/1744-9081-3-53
|View full text |Cite
|
Sign up to set email alerts
|

Catching the news: Processing strategies in listening to dialogs as measured by ERPs

Abstract: Background: The online segmentation of spoken single sentences has repeatedly been associated with a particular event-related brain potential. The brain response could be attributed to the perception of major prosodic boundaries, and was termed Closure Positive Shift (CPS). However, verbal exchange between humans is mostly realized in the form of cooperative dialogs instead of loose strings of single sentences. The present study investigated whether listeners use prosodic cues for structuring larger contextual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 24 publications
6
49
1
1
Order By: Relevance
“…Furthermore, this research showed that prosody usually helps to define the focus structure of a sentence in speech comprehension (Cutler, Dahan, & Van Donselaar, 1997). Electro EncephaloGram (EEG)-experiments further examined the importance of focus and prosody for speech comprehension (Dimitrova, 2012;Heim & Alter, 2006;Magne et al, 2005;Toepel, Pannekamp, & Alter, 2007) and revealed processing difficulties when new information is deaccented or given information accented. For instance, Dimitrova (2012) found late positivities after inappropriately accented words and inappropriately unaccented words in Dutch spoken sentences, reflecting difficulties in understanding sentences with prosodic mismatches.…”
Section: Focus Structure In Language Processingmentioning
confidence: 99%
“…Furthermore, this research showed that prosody usually helps to define the focus structure of a sentence in speech comprehension (Cutler, Dahan, & Van Donselaar, 1997). Electro EncephaloGram (EEG)-experiments further examined the importance of focus and prosody for speech comprehension (Dimitrova, 2012;Heim & Alter, 2006;Magne et al, 2005;Toepel, Pannekamp, & Alter, 2007) and revealed processing difficulties when new information is deaccented or given information accented. For instance, Dimitrova (2012) found late positivities after inappropriately accented words and inappropriately unaccented words in Dutch spoken sentences, reflecting difficulties in understanding sentences with prosodic mismatches.…”
Section: Focus Structure In Language Processingmentioning
confidence: 99%
“…Their interpretation has also varied widely, but most often involving reference to the CPS or P600 components. Several studies (Toepel, Pannekamp, & Alter, 2007;Hruska & Alter, 2004;Toepel & Alter, 2004) have attributed positivities elicited by focus elements to the CPS component, a positivity found in response to prosodic parsing (Pannekamp, Toepel, Alter, Hahne, & Friederici, 2005;Steinhauer & Friederici, 2001;Steinhauer et al, 1999), which they then reinterpreted as a marker of information segmentation at focus positions. Because focus elements in these studies often occurred at phrase boundaries that give rise to prosodic parsing, the exact underlying source of the CPS remains ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that the ERP responses to the inappropriate accentuation (i.e., given informationaccented) might depend on the predictability of the pitch accent: When the given information was far ahead of focused information, the constraint of given information being unaccented was still weak, so the extra accentuation might have captured attention which led to a positive effect; however, when the given information was next to the focused information, the expectation of placing no accentuation on the given information became strong, so the spurious accentuation caused processing difficulty and thus led to a negative effect. However, no specific effect was found in some other studies (Hruska and Alter 2004;Ito and Garnsey 2004;Johnson et al 2003;Toepel et al 2007). …”
Section: Empirical Studies On the Is Influence On Language Processingmentioning
confidence: 61%
“…These studies mainly manipulated the correspondence between pitch accent (in auditory sentences) and information status of a word that was marked in different manners. For missing accentuation (i.e., focused information is unaccented), most studies found negative shifts compared to accented conditions, with varying time windows and scalp topographies: an anterior negative effect between 100 and 500 ms in English (Johnson et al 2003); an anterior negative effect between 250 and 1,500 ms in Japanese (Ito and Garnsey 2004); a centro-parietal N400 effect between 200 and 600 ms in German (Hruska and Alter 2004); a broadly distributed negative effect between 250 and 450 ms (Bögels et al 2011) or between 200 and 500 ms (Dimitrova et al 2012) in Dutch, a sustained central posterior negative deflection lasting about 500 ms in German (Toepel et al 2007); broadly distributed negative effects between 150 and 1,050 ms for sentence-final words in French (Magne et al 2005). However, another two studies found a positive shift during 100-750 ms over left hemisphere in German Alter 2006, 2007).…”
Section: Empirical Studies On the Is Influence On Language Processingmentioning
confidence: 99%
See 1 more Smart Citation